I can't pay! Accessibility analysis of mobile banking apps - Lopes, Renan; Façanha, Agebson Rocha; Viana, Windson (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2022)
Mobile applications have become ubiquitous for the most diverse services of our daily lives. Today, far beyond entertainment and social networks, essential services (e.g., food delivery, official digital documents, health appointments, and banking features) have the mobile environment as their primary access platform. In this context, we need to ensure that people who are blind do not face barriers that make it challenging to use these services, which are increasingly common in the Brazilian routine. Our study aims to analyse the current state of accessibility of banking applications in the national territory. For this, we divided the study into two main parts. Firstly, we carried out an automatic accessibility check of four applications from Brazilian banks using the Accessibility Scanner. Secondly, we implemented a manual accessibility inspec tion of the same four applications. We followed the requirements proposed by the Mobile Accessibility Guide - Sidi and used the Talkback simulating user interaction. The results indicated the pres ence of requirements violations in all applications, especially in their interaction and navigation features. We found a total of 653 violations across all applications. In addition, the Accessibility Scan ner identified an average of 7.72 errors on each screen analysed, including interface components without textual description. These results indicate that the current picture of socio-digital accessibility of banking applications is still far from what would be considered ideal. These results should draw the attention of the scientific com munity and financial institutions to the accessibility problems of mobile banking applications.